Prevention and screening of diabetes through a workplace campaign: an experience in advanced tertiary sector - Cirla, Piero Emanuele; Martinotti, Irene (La Medicina del Lavoro, 2020)
Introduction: Worldwide, diabetes and its complications are a health priority. In Italy, its social global impact on private life and occupation relationships is not always considered. In adults the physiopathology is not completely understood yet, but it surely involves many relevant risk factors. Corporate social responsibility actions can play a significant role in life style through information and education, but the level of uncertainty about the screening cost-effectiveness ratio is high. Objectives: To evaluate a diabetes screening and educational program, in the workplace. Results: An information campaign about diabetes was addressed to 4,232 office workers. In this group, 425 volunteers without a prior diagnosis of diabetes (average age of 44 years, average Body Mass Index 24.4 kg/m2) participated in individual moments with the company physicians (assisted calculation of “Diabetes risk score”, screening by fasting blood glucose, and specific counseling). The prevalence of elevated capillary blood glucose was 16% (n = 68) and new diagnosis of diabetes was made in 1.6% of workers participating in the screening (n = 6). Discussion: A diabetes prevention campaign was carried out on Italian office workers in order to develop targeted preventive strategies. The campaign was aimed at primary and secondary prevention. Conclusions: The collaboration of the “company system” provided useful and effective support for a successful implementation of preventive diabetes campaign. The company’s occupational physician’s involvement was strategic.